Development of a Balanced Learning Model For Physical Education Students - Dwi Nata, Anggri; Muhiri; Dirneti; Eka Lenggang Dianasari; Edi Kurniawan (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
The learning carried out in physical condition formation lectures so far has not provided much variety in learning, so it appears that learning is boring and less enjoyable. This research aims to create a sports balance learning model for physical education students at Karimun University. This research uses the 4D method, in 4D research there are 4 stages, namely define, design, development, and disseminate. The analysis technique used is descriptive analysis. The results of the research are: a) Development of a sports balance learning model for physical education students is feasible and can be used. b) Trials have been carried out on sports balance learning model products for physical education students, which have been tested and proven to be able to improve students' skills. The development of a balance learning model for physical education students has a level of product suitability with learning objectives of 96%, product suitability with students of 90%, product suitability with the material of 92%.